Chapter Coetzee's Disgrace - Meĳer, Maaike (Amsterdam University Press, 2023)
In this essay I discuss Buikema's ideas about the specific function of literature in times of social upheaval and political violence. Buikema resists the current tendency to reduce engaged novels to their political views and statements about the world. To their author's intentions, basically. A literary analysis has to do justice to the ways in which political themes are represented, which largely escape authorial control. Close (inter)textual analysis can arrive at different experiences of a work of art. Buikema illustrated this conviction with an analysis of Coetzee's Disgrace. I continue her analysis and read Disgrace for its stunning literary representation of hegemonic masculinity and how a white macho man is transformed and healed. Women and blacks guide him in this process.